2014
DOI: 10.6007/ijarped/v3-i1/814
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Examination Practices in Annual and Semester System in Public Sector Universities of the Punjab Pakistan

Abstract: The purpose of this study was to find out the examination practices in annual and semester system at public sector universities of the Punjab. The sample of the study was drawn from three public sector universities of the Punjab. All these three universities conduct exams both semester and annual-based. Data was collected from 600 students who appeared in examinations in annual and semester system in selected universities. Questionnaire was designed for students to know their opinion about annual and semester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Consequently, the transparency in semester examination system is compromised. These finding are consistent with the work of Perveen and Saeed (2014), Munshi, Javed et al (2012), Ayubbuzder and Ali (2013) who concluded that the informants of their studies also showed discontent with working of the semester examination system. On the contrary, the semester examination system has been found a valid and reliable system in other countries (Dahal 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, the transparency in semester examination system is compromised. These finding are consistent with the work of Perveen and Saeed (2014), Munshi, Javed et al (2012), Ayubbuzder and Ali (2013) who concluded that the informants of their studies also showed discontent with working of the semester examination system. On the contrary, the semester examination system has been found a valid and reliable system in other countries (Dahal 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaires were distributed randomly among students. It was found that majority of student's favored annual system [22] & semester system as both provides an opportunity to do mastery over subjects, ease in coverage of syllabus and constraints of concepts [12,14,18,22]. A comparative study was conducted in Govt.…”
Section: Discussionmentioning
confidence: 99%
“…Both systems are useful for proper students education assessments but each system has its merits & demerits. [12,22] Self-administered questionnaire attempted to identify the system which provides good quality of education to the students to make them better professionals, and group discussions using a semantic differential scale. The questionnaires were distributed randomly among students.…”
Section: Discussionmentioning
confidence: 99%
“…In those subjects they do not get good marks. Teachers who check the assign mental work regularly and offer feedback have highly intelligent mind students (Perveen & Saeed, 2014). Teachers use different audio visual aids to clear them lesson.…”
Section: Review Of the Related Literaturementioning
confidence: 99%